Analisis Ketercapaian Indikator Standar Pembiayaan pada SD Negeri Pamucatan Kabupaten Bandung Barat - Abdussalaam, Mokhamad Roby (widiyanto, 2019)
School quality is directly related to the quality of education in an education unit. In achieving good school quality, it is necessary to pay attention to teacher quality, student quality, school culture and discipline, and educational facilities and funding. This research focuses on the study of the achievements of indicators on education financing management and learning facilities for school quality. The aim is to find out the description and analyze the influence of education funding management and learning facilities on school quality. This study uses descriptive analysis method with a quantitative approach. Sampling is through indicators of standard funding in elementary school. The analysis technique uses descriptive analysis. The results of this study indicate that the management of education funding at the pamucatan level averages 80% - 90% of the 16 standard financing indicators. Based on these findings, it is recommended that schools pay attention to the stages of education financing management, especially when planning and realization of financing. Whereas the principle of utilizing facilities needs to be considered the efficiency of the use of learning facilities in order to achieve learning objectives and improve the quality of schools.